Acceptability and tolerability of omega-3 fatty acids as adjunctive treatment for children and adolescents with eating disorders. Issue 2 (15th March 2017) - Woo, Julia; Couturier, Jennifer; Pindiprolu, Bharadwaj; Picard, Lindsay; Maertens, Charlotte; Leclerc, Anick; Findlay, Sheri; Johnson, Natasha; Grant, Christina; Kimber, Melissa
ABSTRACT: The objective of this study was to examine the acceptability and tolerability of omega-3 fatty acids as an adjunctive treatment for children and adolescents with eating disorders (EDs). Children and adolescents with EDs received omega-3 supplements (300 mg eicosapentaenoic acid [EPA] and 200 mg docosahexaenoic acid [DHA]/day) in addition to standard treatment for 8 weeks. Primary outcomes were dropout rate, compliance, and side effects. Secondary outcomes included percent ideal body weight, Eating Disorders Inventory-3 (EDI-3), Children's Depression Inventory-2 (CDI-2), and Multidimensional Anxiety Scale for Children (MASC). There were 21 participants with mean age of 15.29 ± 2.0 years. There were no dropouts. Omega-3 was well tolerated by all participants. Compared to baseline, at week 8 there was a significant increase in mean percent ideal body weight but no significant difference in scores on the EDI-3, CDI-2, and MASC. We conclude that omega-3 supplements are acceptable and well tolerated in the pediatric ED population.